Congenital Porencephaly in a New Born Child - Pokhraj P., Suthar (J Clin Diagn Res, 2014)
A 2-day-old male child presented with history of enlarged head and seizures since birth, born by caesarean section. Head circumference was 56 cm (dilated) with widely open anterior and posterior fontanelle. Routine investigations were within normal limits. CT head revealed a large non-enhancing fluid attenuating cystic lesion in posterior parietal and occipital region with communicating to dilated bilateral lateral ventricles and subarachnoid space.